KINERJA KEAGENAN DAN CLEARANCE KAPAL LIVESTOCK PERUSAHAAN PELAYARAN INDONESIA - Suparwan CK; Dian Permata Sari; Berlian Badarusman (Institut Transportasi dan Logistik Trisakti, 2018)
The purpose of the study is to analyze the ship agency performance towards the clearance of livestock ship at PT Serasi Shipping Indonesia. The methods used in the data analysis were simple linear regression and hypothesis testing method. The result of the analysis shows that there is a correlation between the ship agencies towards the clearance of livestock ship. Y= 9,800+0.407X. Based on the t-test analysis, in order to analyze the effect of the whole variables X to variables Y simultaneously, the result is 6,640. Therefore, t count > t table which is 6,640 > 1,701, which means H0 is rejected and H1 is accepted. As a result, there is a simple but strong and positive correlation between the performance of ship agencies towards clearance livestock ships with KP of 61.2%.